LANGUAGE, IDENTITY AND ETHNICITY IN FOOD-TALK IN LUBUKLINGGAU COMMUNITY - Sastika Seli; Linda Agustin (JAMBI-ENGLISH LANGUAGE TEACHING, 2019)
This research aimed to determine the language use of Padang, Javanese and Lubuklinggau ethnic to show their identity in talking about food in Lubuklinggau community. The research was a descriptive qualitative research. The subject of this research was the informants from Padang, Javanese, and Lubuklinggau ethnic that live and has become the citizen in Lubuklinggau. It was done through social network or ‘friend of friend’ technique by Milroy and Milroy. The data collection techniques in this study were done through three techniques; they are Participation Observation, Recording and Noting Techniques. Some ethnographic interviews were also carried out to support the observational data. The result of this research showed three findings including, 1) pride to the food as the part of culture, 2) promoting foods to describe some cultural events, and 3) identifying power through taste. The research is highly expected to be the valuable reference for other researchers to conduct language research in Lubuklinggau.